Characteristics, nature, and formation of palaeosurfaces within dunes on Fuerteventura. Issue 1 (31st October 2018) - Roettig, Christopher-Bastian; Varga, György; Sauer, Daniela; Kolb, Thomas; Wolf, Daniel; Makowski, Vera; Espejo, José Manuel Recio; Zöller, Ludwig; Faust, Dominik
Abstract: The appearances of palaeosurfaces intercalated into palaeo-dune fields on Fuerteventura are multifaceted. Although reddened layers in these dune sediments might suggest that strong soil-formation processes have taken place, the combination of aridity and parent material, namely biogenic carbonate sand of shelf origin, reveals that strong soil formation seems unlikely. These sediments rather represent de- and recalcification processes only. Solely in the case of admixed material of volcanic origin and dust deposits further soil-forming processes seem to be possible. Hematite-rich Saharan dust contributes to reddish colouration of the palaeosurfaces. In addition, CaCO3 -coated iron particles appear to be ingredients of dust being leached after deposition and transformed to hematite. Overall, we propose much weaker soil-forming processes during the Pleistocene than previously postulated. Our findings support the relevance of local environments. Carbonate sands of shelf origin hinder strong soil formation and the reddish layers separating dune generations are palaeosurfaces, which mainly consist of Saharan dust. After deposition of allochthonous material, these layers are overprinted by weak soil-forming processes. The formation of palaeosurfaces primarily depends on morphodynamically stable periods during limited sand supply. Our data suggest a cyclicity of processes in the following order: (1) sand accumulation, (2) dust accumulation and weak soil formation, and (3) water-induced erosion. For the Canary Islands, we support the assumption of glacial maxima being periods of increased levels of moisture. In combination with rising sea level, we propose that favorable conditions of surface stability occur immediately after glacial maxima during periods of starting transgression, whereas regression periods immediately after sea-level high stands seem to yield the highest sand supply for the study area.